Examining the Link Between Religion and Corporate Governance: Insights From Nigeria. Issue 5 (May 2020) - Nakpodia, Franklin; Shrives, Philip J.; Sorour, M. Karim
This article examines whether the degree of religiosity in an institutional environment can stimulate the emergence of a robust corporate governance system. This study utilizes the Nigerian business environment as its context and embraces a qualitative interpretivist research approach. This approach permitted the engagement of a qualitative content analysis (QCA) methodology to generate insights from interviewees. Findings from the study indicate that despite the high religiosity among Nigerians, religion has not stimulated the desired corporate governance system in Nigeria. The primary explanation for this outcome is the presence of rational ordering over religious preferences thus highlighting the fact that religion, as presently understood and practiced by stakeholders, is inconsistent with the principles underpinning good corporate governance.